STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER SISWA DI SEKOLAH MENENGAH PERTAMA BRAWIJAYA SMART SCHOOL MALANG - M. Ata Saiful Mila; Chalimatus Sa’dijah; Atika Zuhrotus Sufiyana (VICRATINA, 2020)
Character education of very important to improve the personal and community environment.  As Islamic Religious Education Teachers have the mandate to teach and educate their students with religious knowledge so that they have good morals for life in the future.  Therefore, Brawijaya Smart School Malang Junior High School is present as a place to educate a generation of moral people based on faith and piety.  This research aims to reflect the value of character, Islamic religious education teacher strategies and problems and solutions in character building in Brawijaya Junior High School Poor Smart School.  To achieve this goal, researchers use field research methods (field research) with the type of case study research.  In collecting data, researchers used the method of observation, documentation, and interviews / interviews.  The data analysis method used is reducing data, presenting data, and drawing conclusions.  From the results of the study showed that the character values instilled by PAI teachers were Religious Value, Honesty, Discipline, Responsibility, Concern, Curiosity, Self-confidence, Love of Cleanliness and tidiness, and Tolerance.  PAI teacher strategy in shaping students' character by way of example, planting discipline, habituation, creating a conducive environment, integration and internalization.